Мармулядовий апокаліпсис або терапія постмодерном у романі Софії Андрухович «Фелікс Австрія» - Левченко, Галина Дмитрівна; Levchenko, Galуna (Східноєвропейський національний університет імені Лесі Українки, 2016)
Об’єктами розгляду в статті постають постмодерна рецепція й трансформація таких образно-смислових домінант модерної культури зламу ХІХ–ХХ ст., як осмислення історії, психологізму, жіночої емансипації в романі «Фелікс Австрія» Софії Андрухович. Образна парадигма твору прочитується як своєрідний художньо-терапевтичний шлях подолання невротичних нав’язливих ідей та соціальних стереотипів, актуалізованих епохою модернізму. The object of the analysis in the article is postmodern reception and transformation of such figurative and semantic dominants of modern culture of the end of the XIX – the beginning of the XX centuries as trying to find the sense of history, psychologism, women`s emancipation in the novel «Felix Austria» by S. Andruhovych. The surface structure of the literary work and the images that have been modeled in it demonstrate the specific artistic way of liberation from neurotic obsessions and stereotypes that have been actualized by the epoch of modernism. Characteristic atmosphere of moral decline and apocalypse premonition for Ukrainian fin de siècle is depicted both with the help of individual psychological conflicts that are experienced by main heroines, neurotic background of their interaction and also with the help of the image-symbol of the house that is prone to ruinous influence of different elements, the images of robbed temples and utopian «happy Austria» of the last decades of the existence of Habsburg Empire. The presentiment of downfall of «old world» in the novel of S. Andruhovych gets filled with postmodern sense. The literary work itself has own metaphor of illusionist theatre that corresponds to the principle of structuring of the world in the novel as multi-way mirror maze for the movement of which the feeling of relativity of values, rules, laws, psychological and moral norms is responsible.
Marmalade Apocalypse or Therapy by Postmodern in the Novel by Sophiya Andruhovych «Felix Austria»
Keywords: історизм; психологізм; фемінізм; постмодерний релятивізм; іронія; інтертекст; historism; psychologism; feminism; postmodern relativity; irony; intertext